Nutritional balance and yield for green manure orange trees - Ragozo, Carlos Renato Alves; Leonel, Sarita [UNESP]; Tecchio, Marco Antonio [UNESP] (Universidade Federal de Santa Maria, 2014)
Intercropping could efficiently prevent soil nutrient losses caused by extensive agriculture. The present study aimed to assess the effect of green manure on the nutritional status of orange trees cultivar 'Pera' (Citrus sinensis (L.) Osbeck). The plants were grafted on 'Cravo' lime trees and were then planted in a 7x4m space. Four different treatments corresponding to the evaluated green manures were employed: jack bean (JB) (Canavalia ensiformis DC), lablab (LL) (Dolichos lablab L.), pigeon pea (PP) (Cajanus cajan L. Millsp), and Brachiaria (BQ) (Brachiaria brizantha Hochst ex A. Rich. Stapf) as control. The experimental design was in randomized blocks, in split-plot time, with six replicates, with four treatments (green manures) and two plants per evaluation. The nutritional status was assessed by using the DRIS method (Diagnosis and Recommendation Integrated System); the yield and the macro and micronutrient levels contained in green manures and in the control was also determined. The nutritional diagnosis indicated that, in the two years of experiment, plants treated with green manure showed better nutritional balance index compared to Brachiaria. This suggests that, over time, green manure can lead to better nutritional balance. Pigeon pea treatment showed the highest yields, compared to control, in the two evaluated crop cycles (2004/05 and 2005/06).

O manejo de culturas intercalares poderia prevenir eficientemente as perdas de nutrientes do solo, causadas pelo cultivo extensivo. O trabalho teve como objetivo avaliar o efeito da utilização de adubos verdes no estado nutricional de plantas de laranjeira 'Pêra' (Citrus sinensis (L.) Osbeck). O solo da área de cultivo é denominado Neossolo Quartzarênico. As plantas estavam enxertadas em limoeiro 'Cravo' e foram plantadas num espaçamento de sete por quatro metros. Foram empregados quatro tratamentos correspondentes aos adubos verdes avaliados, sendo eles: feijão de porco (FP) (Canavalia ensiformis DC), labe-labe (LL) (Dolichus lablab L.), feijão guandu anão (GA) (Cajanus cajan L. Millsp) e braquiária (BQ) (Brachiaria brizantha Hochst ex A. Rich. Stapf). Conduziu-se o experimento em delineamento de blocos casualizados em esquema de parcelas subdivididas no tempo, com seis repetições, quatro tratamentos (adubos verdes) e duas plantas úteis para as avaliações. Avaliou-se o estado nutricional pelo método DRIS (Sistema Integrado de Diagnose e Recomendação), bem como a produção e o teor de macro e micronutrientes contidos nos adubos verdes e na testemunha. O diagnóstico nutricional demonstrou que, nos dois anos de experimentação, houve um melhor índice de balanço nutricional para os adubos verdes, quando comparados com a braquiária (testemunha). Esta constatação permite inferir sobre a disponibilidade de, ao longo do tempo, os adubos verdes permitirem um melhor equilíbrio nutricional para as plantas. O tratamento com feijão de porco apresentou as maiores produções, quando comparado com a testemunha, nos dois ciclos agrícolas de avaliação (2004/05 e 2005/06).
Balanço nutricional e produtividade em laranjeiras manejadas com adubação verde
Keywords: Citrus sinensis; Citrus limonia; culturas intercalares; sistema integrado de diagnose e recomendação; Citrus sinensis; Citrus limonia; intercropping; diagnosis and recommendation integrated system